2022
DOI: 10.1039/d2cp00792d
|View full text |Cite
|
Sign up to set email alerts
|

Pt- and Pd-modified transition metal nitride catalysts for the hydrogen evolution reaction

Abstract: Hydrogen production via the electrochemical splitting of water using renewable electricity represents a promising strategy. Currently, Platinum group metals (PGM) are the best performing hydrogen evolution reaction (HER) catalysts. Thus,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 105 publications
2
10
0
Order By: Relevance
“…[59] As well documented in previous studies, [60][61][62] the high binding energy of this intermediate to the transition metals and their nitrides does not allow the reaction to advance to desorption, which is the dominating reason for inhibiting the HER and increased resistance. A recent computational study, based on density functional theory, [1] showed higher hydrogen binding energy for CrN than TiN [63] further supports our findings.…”
Section: Electrolytesupporting
confidence: 89%
“…[59] As well documented in previous studies, [60][61][62] the high binding energy of this intermediate to the transition metals and their nitrides does not allow the reaction to advance to desorption, which is the dominating reason for inhibiting the HER and increased resistance. A recent computational study, based on density functional theory, [1] showed higher hydrogen binding energy for CrN than TiN [63] further supports our findings.…”
Section: Electrolytesupporting
confidence: 89%
“…Platinum (Pt) is the well-recognized HER catalyst since there is almost no overpotential at startup and the current rises rapidly with increasing voltage. Reducing the loading of platinum is the only viable method for reducing prices, and researchers have made several efforts to build new catalysts to develop inexpensive and plentiful alternatives to Pt [ 109 , 110 ]. Although it is commonly asserted that potential non-Pt catalysts have been developed, none can match the inherent activity and stability of Pt/C.…”
Section: Progress In Catalysts For the Hermentioning
confidence: 99%
“…Large abundant non-noble transition metals and their compounds have been explored as electrocatalysts for facilitated HER such as transition metals/alloys, , carbides, nitrides, , phosphides, , sulfides, , selenides, etc. For instance, we have constructed a hierarchical nanosheet structure of vanadium carbide (VC) graphitic carbon nanosheet (gCNS) composed of isolated VC nanoparticles encapsulated by a mesoporous gCNS with high conductivity for HER in an acidic electrolyte .…”
Section: Introductionmentioning
confidence: 99%
“…However, the expensive price and small reserves of Ptgroup metals have limited their universal application to HER, and therefore, it is significant to construct nonprecious transition metal-based catalysts for highly efficient HER. 7−9 Large abundant non-noble transition metals and their compounds have been explored as electrocatalysts for facilitated HER such as transition metals/alloys, 10,11 carbides, 12−14 nitrides, 15,16 phosphides, 17,18 sulfides, 19,20 selenides, 21−23 etc. For instance, we have constructed a hierarchical nanosheet structure of vanadium carbide (VC) graphitic carbon nanosheet (gCNS) composed of isolated VC nanoparticles encapsulated by a mesoporous gCNS with high conductivity for HER in an acidic electrolyte.…”
Section: ■ Introductionmentioning
confidence: 99%